Comparison of different cooling strategies in achieving desired crystal size distribution for seeded potash alum crystallization process - Siti Zubaidah, Adnan; Noor Asma Fazli, Abdul Samad (AIP Publishing, 2025)
Crystallization process is governed by nucleation, growth and dissolution mechanisms that are supersaturation dependent. It is thus crucial for the cooling strategy to be capable of controlling these mechanisms. However, to properly control these mechanisms through one cooling strategy is a challenge as increasing supersaturation would increase both nucleation and growth rates, while reducing supersaturation may increase dissolution and nucleation rates. This would contribute to the problem of achieving crystal size distribution (CSD) with significant fines. The trade-off between these rates needs to be balanced and employing several cooling strategies to compare which strategy works well with the selected crystallization process is recommended. This paper aims to provide a performance comparison in terms of CSD for two established cooling strategies labelled I and II, against new strategy III in achieving large sized crystals with less fines for seeded potash alum crystallization process. Strategy I is linear cooling policy, strategy II is for maximizing CSD, and strategy III is for minimizing supersaturation. This comparison study is established by simulation via MATLAB software. Based on the simulation results, strategy I delivers the smallest size of CSD with high fines or small-sized crystals, while strategy II provides large CSD but with significant number of fines. Strategy III gave smaller size of grown seed crystals compared to strategy II but with insignificant fines. Overall, strategy III is considered the best trade-off strategy for seeded potash alum crystallization process in producing large size of crystals with the lowest number of fines.